Bacterial analysis of high vaginal swabs from women of reproductive age at a tertiary hospital in Lucknow - Verma, Sneha; Hassan, Sarah; Shukla, Priyanka; Ahmad, Ayesha; Nag, Riya (International Journal of Research in Medical Sciences, 2025)
Background: Vaginal infections are prevalent among women, often caused by disruptions in the vaginal microbiota, leading to symptoms like abnormal discharge, itching, and discomfort. Bacterial vaginosis (BV) is a common condition characterized by a shift from Lactobacillus dominance to anaerobic bacteria overgrowth, affecting reproductive-age women significantly. Understanding the microbial ecology and antibiotic susceptibility of vaginal pathogens is crucial for effective management. The study aims to identify bacterial profiles and antibiotic susceptibility patterns from high vaginal swabs. Objectives include determining prevalent pathogenic bacteria and analyzing their antibiotic susceptibility. Methods: A cross-sectional study at Era’s Lucknow Medical College and Hospital over six months analyzed 73 high vaginal swabs from gynecological clinic attendees. Data collection covered demographics, clinical symptoms, and antibiotic history. Laboratory methods included Gram staining, culture on selective media, biochemical tests, and antibiotic susceptibility testing using the Kirby-Bauer disc diffusion method per CLSI guidelines. Results: In this study at Era’s Lucknow Medical College and Hospital, 73 high vaginal swab samples were cultured, with 37 (50.7%) testing positive for various pathogens. Escherichia coli was the predominant organism (57%), followed by Enterococcus species (22%), Klebsiella pneumoniae (13%), Staphylococcus aureus (5%), and Pseudomonas aeruginosa (3%). Antibiotic susceptibility testing revealed high effectiveness against Gram-negative bacteria, particularly for imipenem, meropenem, and colistin, with rates exceeding 80%. Conclusions: Escherichia coli was found to be the most common cause of abnormal vaginal discharge in women of the reproductive age group.